"Economic Policy and Industrial Growth in Pakistan"—A Review (Review Article) (The Pakistan Development Review, 1970)
Stephen R. Lewis (Jr.) is one of the few foreign economists most compe¬tent to write on Pakistan economy judged on the basis of his past publications, length of association with this country and sincerity of commitment to under¬stand it. Therefore, the volume under review [10], coming from the pen of such a knowledgeable person, cannot but be seriously taken by all students of the Pakistan economy. The general purpose of the work has been to explore the causes of rapid industrialization in Pakistan, to analyse the process of industrial growth and to assess the relative importance of policy variables and nonpolicy determinants in explaining the pattern and speed of industrialization. Lewis extensively draws upon the previous studies on Pakistan economy relating to the structure of tariffs and commodity taxes, the growth and structural changes in manufacturing industries, the intersectoral terms of trade between agriculture and manufacture and the effective rates of protection to industries (many of which were done either by him or with his inspiration or collaboration), so much so that the book looks like a lengthy digest of these studies carried out in the past. However, he marshals the empirical findings of these works to deduce some new conclusions.